KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI OPERASI HITUNG BILANGAN KELAS III UPT SD NEGERI 160 GRESIK - Zuraidah, Yasmin Wahyu (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine students' mathematical problem-solving abilities in material arithmetic operations grade 3 elementary school 160 Gresik, to describe students' problem-solving abilities using Polya stages. This research includes descriptive qualitative research in which the research describes the phenomena that occur. Data collection techniques with tests and interviews. The target of this research is grade 3 students. The methods used are tests and interviews. The results showed that the students' mathematical problem-solving abilities on arithmetic operations for grade 3 were quite good with the analysis results being categorized into, High ability (KT) was 5 students with a presentation of 20%, and Medium ability (KS) was 7 students with presentation of 28%, while the Low ability (KR) is as many as 13 students with a presentation of 52%. Analysis of problem-solving abilities through the Polya stages is able to become a new insight for teachers in understanding students' problem-solving abilities in material arithmetic operations. However, there are limitations in this study that can only be applied to problems that are problem solving in nature